PROSOCIAL BEHAVIOR OF EARLY CHILDREN VIEWED FROM PLAYING ACTIVITIES WITH FRIENDS AT SCHOOL TK ISLAM SITI HAJAR - Sitepu, Juli Maini (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to determine the prosocial behavior of early childhood in terms of play activities with friends at school. This type of research used is quantitative research. The population and sample in this study were all children in group B at Siti Hajar Islamic Kindergarten. The data collection method uses a questionnaire as filled in by the parents of the students. The data analysis technique used is simple linear regression. Based on the results of the study, it was shown that Ha was accepted, which means that playing with friends can determine the prosocial behavior of children in group B at Siti Hajar Islamic Kindergarten. Based on the results of a simple linear regression test with a significance value or P = 0.000 where p 0.05. The research results show that the homogeneity test is 0.080 or sig 0.05, which means that the data comes from populations that have the same or homogeneous variance. The influence of playing with friends at school on prosocial behavior of early childhood is 47.8%, which is obtained from the test results of the coefficient of determination which is equal to 0.478 or if it is percentaged at 47.8%. While the remaining 52.2% is influenced by other factors not examined in this study.